Nurturing Religious Souls in Public Schools: The Meaning of Religious Extracurricular Activities for Students’ Spiritual Intelligence - Moh Farhan; Mukni'ah; Mursalim (Program Studi PGMI, 2025)
This study examines the development of students’ spiritual intelligence through religious extracurricular activities in a public-based Islamic elementary school. The research was conducted at MI Bustanul Ulum 09 Curah Lele Balung using a qualitative Phenomenoapproach. Data were collected through in-depth interviews, participant observation, and documentation involving ten participants, consisting of one principal, three teachers supervising religious extracurricular activities, and six actively involved students. The data were analyzed using interactive techniques of data reduction, data display, and verification. The findings indicate that religious extracurricular activities such as tahfidz, yasinan, collective dhuha prayer, and Islamic storytelling function not only as routine religious practices but also as experiential learning processes that foster students’ spiritual intelligence. Students demonstrate increased sincerity, discipline, empathy, and religious awareness through sustained participation. Teachers play a central role as spiritual mentors (murabbi) by modeling values and facilitating reflective dialogue, while parental and community involvement strengthens value consistency between school and home. This study implies that religious extracurricular programs should be managed as integral components of character and spiritual education rather than supplementary activities. Strategically integrating reflective practices into these programs can enhance their transformative impact on students’ spiritual development. Future research is recommended to involve a larger number of participants and diverse school settings, as well as to employ longitudinal or mixed-method approaches to examine the long-term effects of religious extracurricular activities on students’ spiritual intelligence.